SOCIO-PSYCHOLOGICAL DETERMINANTS OF ADOPTING AI-DRIVEN ROBOTIC ASSISTANTS IN GERIATRIC CARE: A REVIEW OF CURRENT TRENDS AND ETHICAL CHALLENGES - Reczka, Karolina; Zalewska , Zuzanna; Szymkowiak , Julia; Woźniak , Maria (International Journal of Innovative Technologies in Social Science, 2026)
In the face of a rapidly aging population, artificial intelligence (AI)-based robotic assistants represent an innovative solution to support geriatric care systems. Despite their growing potential to assist both patients and healthcare staff, the widespread integration of these technologies still faces complex barriers. This review article aims to analyze the socio-psychological determinants influencing the acceptance of AI-powered robots in elder care, as well as to identify key ethical challenges associated with this phenomenon. The review is based on an analysis of the current literature, focusing on studies evaluating human-robot interaction (HRI) among seniors. The results indicate that the psychological factors most strongly influencing the adoption of this technology are: perceived usefulness, fear of new and unknown solutions, and the level of trust in intelligent machines. From a social perspective, the potential of robots to reduce feelings of loneliness is of key importance, while simultaneously posing a risk of limiting authentic, interpersonal interactions. In the area of ethics, the most frequently raised issues include threats to privacy, data security, and serious concerns regarding the dehumanization and objectification of geriatric patient care. In summary, the successful implementation of robotic assistants requires a balanced approach that incorporates empathy and the human dimension of care while minimizing ethical risks. Technology design for older adults must strictly adhere to a user-centered model to ensure trust and tangibly improve seniors’ quality of life.